Connection Body Mass Index with Incident Hypertension on Elderly at Sail Community Health Center , Pekanbaru 2025 - Arnila Melina; Ami Amelia (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is characterized by elevated blood pressure, specifically when systolic blood pressure exceeds 140 mmHg and diastolic blood pressure exceeds 90 mmHg. At the Puskesmas Sail in Pekanbaru City, there were 1,276 patients diagnosed with hypertension in 2024. Hypertension remains the third most common disease at the Puskesmas Sail . Additionally, elderly patients dominate the patient population at this Community Health Center . One of the factors contributing to increased blood pressure is body mass index (BMI). Therefore, the researchers were interested in conducting a study on the relationship between BMI and the incidence of hypertension at Puskesmas Sail. To determine the relationship between BMI and the incidence of hypertension among the elderly in the service area of the Puskesmas Sail in Pekanbaru City. This study used an analytical observational design with a cross-sectional study design. The study was conducted at Puskesmas Sail in Pekanbaru. The sample was selected using accidental sampling. Data analysis was performed using the chi-square test. There is a relationship between BMI and the incidence of hypertension among the elderly in the service area of the Puskesmas Sail in Pekanbaru City.